2014
DOI: 10.1155/2014/107501
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Tetramethylpyrazine on Myocardial Ischemia‐Reperfusion Injury

Abstract: Myocardial ischemia-reperfusion injury (MIRI) is a common pathological and physiological phenomenon. Tetramethylpyrazine is the extract of the traditional Chinese medicine Chuanxiong, which can exert protective effects on MIRI in multiple ways. This paper reviewed the current research progress and evidence about the cardiovascular effects of tetramethylpyrazine, which included protecting mitochondria and improving energy metabolism, scavenging oxygen free radicals (OFRs) to inhibit lipid peroxidation, attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…The initial ischemic damage followed by further damage induced by reperfusion is referred to as myocardial I/R injury (Qian et al, 2014). It is believed that I/R-induced myocardial injury is related to the increased reactive oxygen species generation, calcium overloading, apoptotic and necrotic myocytes death, and the loss of membrane phospholipids, especially during reperfusion (Ferdinandy et al, 2007;Balakumar et al, 2008;Rohilla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The initial ischemic damage followed by further damage induced by reperfusion is referred to as myocardial I/R injury (Qian et al, 2014). It is believed that I/R-induced myocardial injury is related to the increased reactive oxygen species generation, calcium overloading, apoptotic and necrotic myocytes death, and the loss of membrane phospholipids, especially during reperfusion (Ferdinandy et al, 2007;Balakumar et al, 2008;Rohilla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tetramethylpyrazine (TMP) is a bioactive constituent found in the root of the Chinese herb Chuanxiong, which is widely used in the treatment of a series of disease for its anti-viral, anti-bacterial, anti-inflammatory, and antioxidant effects [10][11][12][13]. Recent studies have shown that TMP has the protective effect on the kidney injury in diabetic animal model, indicating that TMP may be beneficial for the clinical treatment of DN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Tetramethylpyrazine (TMP) is a bioactive constituent found in the root of the Chinese herb Chuanxiong, which is widely used in the treatment of cardiovascular and cerebral diseases for its anti-viral, anti-bacterial, anti-inflammatory, and anti-oxidant effects (Shang et al 2013;Qian et al 2014). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%